Pembentukan Desa Mitra melalui Penguatan dan Pelatihan Kader Posyandu Berbasis Media Sosial TikTok sebagai Sarana Promosi Inovasi Pangan Lokal NIKCAMBID Empowerment of Partner Village through TikTok-Based Posyandu Cadre Training as a Means to Promote Loca - Oslida Martony; Rina Doriana Pasaribu; Bernike Doloksaribu; Erlina Nasution; Alfira (LPPI UMN AL WASHLIYAH, 2026)
Stunting remains a serious public health issue in Indonesia, particularly in rural areas. This community service program aimed to establish a Partner Village by empowering and training Posyandu cadres, using TikTok as a platform to promote a local food innovation called NIKCAMBID (fish nuggets mixed with durian seed flour). The activity was conducted in Sei Naga Lawan Village, Serdang Bedagai Regency, using a participatory action research approach. Main activities included training in the production of nutritious food products, education on nutritional content, and digital promotion via TikTok. Evaluation results showed a significant increase in cadre knowledge and attitude (p<0.05), with an average knowledge score increase of 34.67 and attitude increase of 22.00. This activity contributes to public awareness of stunting prevention through the use of local food and digital media.